Peranan Dan Fungsi Kurikulum Secara Umum Dan Khusus - Maya Amarta; Ayu Lestari; Indah Cahyani; Mustafiyanti Mustafiyanti (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
One important component in the education system is the curriculum. The curriculum is an educational component that is used as a reference by every educational unit, both by managers and organizers, especially by teachers and school principals. Therefore, since Indonesia has the freedom to provide for its nation's children, the government has begun to develop a curriculum. In this case, the curriculum is created by the central government in a centralized manner and applied to all children throughout Indonesia. In other words, the curriculum system is essentially the education system itself. The curriculum is a very important tool for the success of an education. Without an appropriate and appropriate curriculum it will be difficult to achieve the desired educational goals and objectives.